ANALYSIS OF SOCIO-JURIDIC OF UNDER-AGE MARRIAGE TO CAUSE THE PREGNANCY OUTSIDE OF MARRIAGE (A STUDY IN BULAGI DISTRICT) - Tolodo, Wardin; Akbar, Muhammad; Typhoon B, M. (Risâlah, Jurnal Pendidikan dan Studi Islam, 2022)
This paper aims to investigate the analysis socio-juridic of under-age marriage caused to pregnancy outside of marriage (study in Bulagi district, banggai islands). This study was qualitatif approach with case study. The results showed that underage marriages have legal consequences for husband and wife relations, children's position, and assets. However, on the other hand, it is necessary to solve the problem and prevent child marriage, among others, by making strategic policies in various fields. Prevention of underage marriage can be achieved through changing the way people are aware of their legal behavior, socializing sex education and reproductive health, and providing access to affordable education.